Diagnostic Validity of Ratio between Differences of Central Venous to Arterial CO2 and Arterial to Central Venous O2 Content in Diagnosis of Anaerobic Metabolism among Septic Patients (Journal of Current and Advance Medical Research, 2021)
Background: Detection of anaerobic metabolism is very crucial for the management of the septic patients.Objective: The purpose of the present study was to validate the ratio between differences of central venous to arterial CO2 and arterial to central venous O2 content in diagnosis of anaerobic metabolism among septic patients.Methodology: This prospective observational study was conducted in the Intensive Care Unit of the department of Anaesthesia Analgesia, Palliative and Intensive Care Medicine at Dhaka Medical College Hospital, Dhaka, Bangladesh from January 2016 to December 2016. All patients admitted to ICU with the features of severe sepsis and septic shock according to SSC guidelines with the age of more than or equal to 18 years in both sexes were included in this study. The arterial and central venous blood gases were measure simultaneously. At the same time serum lactate was measured.Result: Among the 69 patients, 31(44.9%) were of severe sepsis and 38(55%) were of septic shock patients. In the severe sepsis and septic shock patients the mean P(v-a)CO2/C(a-v)O2 is 1.39±0.41 and 1.11±0.40 respectively. Serum lactate in case of severe sepsis and septic shock patients is 2.85±1.40 and 3.85±1.04 respectively. The ROC analysis showed an area under curve 0.89 and P(v-a)CO2/C(a-v)O2 ratio cutoff value of 1.21 showed sensitivity 0.84 and specificity 0.94.Conclusion: The P(v-a)CO2/C(a-v)O2  ratio is also a another marker of global anaerobic metabolism and it would be used for diagnosis as well as management of septic patient. Journal of Current and Advance Medical Research, January 2021;8(1):34-38